Toxicity of Micro/Nanobubble Fermentation and Tithonia diversifolia Leaf Extract Against Thrips sp. - Setyaningrum, Sekar Putri; Ikawati, Silvi; Tarno, Hagus (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
One of the main pests impacting agricultural crops is Thrips sp., and controlling it still mostly relies on synthetic pesticides that could have a detrimental impact on both human health and the sustainability of the environment. Although botanical pesticides made from Tithonia diversifolia have been regarded as a viable substitute, nothing is known about how extraction solvents and microbubble technology affect their insecticidal efficacy. Thus, this work assessed the efficacy of fermented distilled water extracts supported by microbubbles and T. diversifolia leaf extracts made with various solvents against Thrips sp. Using a Completely Randomized Design (CRD), experiments were carried out in September–November 2024 and July–October 2025. Mortality data were examined at a 5% significance level (α = 0.05). According to the findings, at a concentration of 200,000 ppm, the fermented extract resulted in 81.25% mortality 48 hours after application (HAA). The n-hexane extract at 1,500 ppm caused the greatest mortality of all the treatments, reaching 96.66% at 48 HAA. This suggests that n-hexane was the best solvent to extract insecticidal bioactive components from T. diversifolia.